Subcellular Targeting of the Euplotes raikovi Kinase Er-MAPK1, as Revealed by Expression in Different Cell Systems - Candelori, Annalisa; Yamamoto, Takaharu G.; Iwamoto, Masaaki; Montani, Maura; Amici, Augusto; Vallesi, Adriana (Frontiers in Cell and Developmental Biology, 2019)
In the ciliate Euplotes raikovi, a 631-amino acid Er-MAPK1 protein kinase was found to localize in nucleoli of the transcriptionally active nucleus (macronucleus) and act as a key component of an autocrine, cell-growth promoting self-signaling mechanism. While its 283-amino acid N-terminal domain includes all the structural specificities of the mitogen-activated protein kinases required for a catalytic function, the 348-amino acid C-terminal domain is structurally unique with undetermined functions. By expressing the two Er-MAPK1 domains tagged with the green fluorescent protein in mammalian fibroblasts, the yeast Schizosaccharomyces pombe and the ciliate Tetrahymena thermophila, evidence was obtained that the C-terminal domain contains all the sequence information responsible for the Er-MAPK1 subcellular localization. However, in fibroblasts and S. pombe this information determined a nucleolar localization of the GFP-tagged C-terminal domain, and a ciliary localization in T. thermophila. In the light of these findings, the Er-MAPK1 localization in E. raikovi was re-examined via immunoreactions and shown to be ciliary besides that nuclear, as is the case for the mammalian intestinal cell kinase with which the Er-MAPK1 N-terminal domain shares a strong sequence identity and a catalytic function.